The Role of Electronic Training in Achieving Professional Development for English Language Teachers at the Intermediate Stage in Al-Kharj Governorate - Al-Harbi, Ebtisam Rubayea; Omar, Eman Helmy Ali (Journal of Educational and Psychological Sciences, 2022)
The aim of this research is to identify the role of e-training in achieving professional development for English language teachers in Al-Kharj Governorate. And to identify the obstacles that limit the application and the proposals that help e-training in achieving professional development for English language teachers. The researcher used the descriptive analytical method, and the questionnaire as a research tool, which was distributed to a sample of (95) English language teachers in the middle school in Al-Kharj Governorate. The study reached the following results: The role of e-training in achieving professional development for English language teachers from their point of view got an average of (2.48) with a small degree. The obstacles that limit the role of e-training in achieving professional development for female teachers got an average of (3.17) with a medium degree. The proposals that help e-training achieve professional development for female teachers got an average of (3.27), with a medium degree. Based on the results, the researcher recommended the necessity of strengthening the plans necessary to employ electronic training in the process of training English language teachers at the intermediate stage, in addition to proposals for complementary studies on the subject.